Pembelajaran Sosiologi Pendidikan Pada Calon Guru Ilmu Pengetahuan Sosial di UINSU - Eka Susanti; Anna Wahyuni; Rina Aulia (CV. Ulil Albab Corp, 2023)
This research aims to conduct an evaluative analysis of educational sociology learning among prospective social science teachers at the North Sumatra State Islamic University (UINSU) using a quantitative approach. A total of 70 students formed the population, and a sample of 30 students was selected using purposive sampling techniques. The data collection instrument is in the form of a questionnaire with structured questions covering aspects of evaluating course material, teaching methods, student empowerment, relevance of material to preparation to become a social studies teacher, satisfaction with teachers and tutors, availability of resources, collaboration between students, teaching preparation, and readiness to face challenges. in the future. The results of data analysis show that the overall evaluation of educational sociology lecture material received a